2022
DOI: 10.1371/journal.pone.0273315
|View full text |Cite
|
Sign up to set email alerts
|

X-ray directional dark-field imaging using Unified Modulated Pattern Analysis

Abstract: X-ray directional dark-field imaging is a recent technique that can reveal a sample’s small-scale structural properties which are otherwise invisible in a conventional imaging system. In particular, directional dark-field can detect and quantify the orientation of anisotropic structures. Here, we present an algorithm that allows for the extraction of a directional dark-field signal from X-ray speckle-based imaging data. The experimental setup is simple, as it requires only the addition of a diffuser to a full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In this work, we presented a newly established X-ray setup at the Elettra synchrotron (Trieste, Italy) implemented in the framework of the S-BaXIT project funded by the European Research Council. This setup is well-suited for a wide range of imaging applications, including absorption radiography and micro-CT, propagation-based imaging, various XPCI techniques such as SBI and speckle-based directional dark-field [19], and spectral imaging. The first SBI images taken with the long branch setup demonstrated that, under the same experimental conditions, XPCDs outperform the conventional FPD in terms of image quality for both differential-phase and dark-field images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we presented a newly established X-ray setup at the Elettra synchrotron (Trieste, Italy) implemented in the framework of the S-BaXIT project funded by the European Research Council. This setup is well-suited for a wide range of imaging applications, including absorption radiography and micro-CT, propagation-based imaging, various XPCI techniques such as SBI and speckle-based directional dark-field [19], and spectral imaging. The first SBI images taken with the long branch setup demonstrated that, under the same experimental conditions, XPCDs outperform the conventional FPD in terms of image quality for both differential-phase and dark-field images.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, figure 5 shows a spectral decomposition with three materials for the same sample employed in the SBI scans. For the spectral acquisition, three conventional absorption images were acquired with three different energy thresholds (𝑡ℎ𝑟 1 = 13 keV, 𝑡ℎ𝑟 2 = 23 keV, 𝑡ℎ𝑟 3 = 26 keV), dividing the spectrum into three energy bins ( [13][14][15][16][17][18][19][20][21][22][23] keV, [23-26] keV, and >26 keV) with the same amount of photons. The total exposure time per projection was 60 s. The material decomposition has been carried out using the minimum residual spectral decomposition algorithm presented in [18], setting three material bases: CaCO 3 (present in insect carapace), water, and carbon (present in wood and plastics).…”
Section: Jinst 19 C01018mentioning
confidence: 99%
“…The dark-field images were extracted using the directional dark-field extension to the unified modulation pattern analysis (UMPA) algorithm, presented by Smith et al (2022) and based on the works by Zdora et al (2017) and De Marco et al (2023). UMPA is a versatile algorithm, proven to work with a variety of x-ray sources (Zdora et The algorithm works by comparing windows in the images the pattern produces with and without the sample in the beam.…”
Section: Dark-field Imagingmentioning
confidence: 99%
“…This is because multiple quantities (T, σ major , σ minor , θ, phase) must be extracted at a given location in the image, and hence multiple measurements must be taken, in this case spatially separated over multiple adjacent pixels. In the case that a higher spatial resolution was required, the measurements would need to be temporally separated over multiple exposures captured for different reference pattern positions (Smith et al 2022). A multiple-exposure approach would be incompatible with the movement seen exposure-to-exposure with this small-area live animal imaging.…”
Section: Dark-field Imagingmentioning
confidence: 99%
“…Therefore diffusive dark-field signal extraction has potential use in multiple fields, such as biomedical studies, material science and industrial inspection. Further to this, in recent years dark-field retrieval methods have been extended to recover directional diffusive dark-field signal, enabling the orientation of SAXS/USAXS-producing texture or fibers to also be visualized [20][21][22][23][24][25]. In the single-mask approach, a mask patterns the X-ray intensity incident on the sample, then an image captured some distance downstream of the sample reveals how it has distorted this pattern.…”
Section: Introductionmentioning
confidence: 99%